On the asymptotic topology of groups and spaces. Part II - Otera, Daniele Ettore (Lietuvos matematikos rinkinys, 2014)
This note continues the study of the topology at infinity of groups and manifolds. Here we will quickly review the notion of geometric simple connectivity together with some more recent developments of it for groups.
Keywords: geometric connectivity; quasi-simple filtration (qsf); inverse representations; 3-manifolds; finitely presented groups